Effect of Tricalcium Phosphate on Healing of Non-Unions: An Observational Study of over 400 Non-Unions - Ferbert T; Münch C; Findeisen S; Pauly W; Miska M; Grossner T; Tanner MC; Schmidmaier G; Helbig L (Dove Medical Press, 2023)
Thomas Ferbert, Christina Münch, Sebastian Findeisen, William Pauly, Matthias Miska, Tobias Grossner, Michael C Tanner, Gerhard Schmidmaier, Lars Helbig Clinic for Trauma and Reconstructive Surgery, Center for Orthopedics, Trauma Surgery and Spinal Cord Injury, Heidelberg University Hospital, Heidelberg, D-69118, GermanyCorrespondence: Lars Helbig, Clinic for Trauma and Reconstructive Surgery, Center for Orthopedics, Trauma Surgery and Spinal Cord Injury, Heidelberg University Hospital, Schlierbacher Landstrasse 200a, Heidelberg, D-69118, Germany, Tel +496221/5635371, Fax +496221/5626300, Email lars.helbig@med.uni-heidelberg.dePurpose: A central aspect of the treatment of non-unions is the filling of bone defects. The quantity of available autologous bone for this purpose is limited. Alternatively, or additionally, bone substitutes may be used. The aim of this retrospective, single-center study including 404 non-unions in 393 patients is to investigate the effect of tricalcium phosphate (TCP) on the healing of non-unions. Furthermore, the influence of gender, age, smoking status, comorbidities, type of surgical procedure, presence of infection, and length of treatment was investigated.Methods: We evaluated three groups of patients. Group 1 received TCP + BG, group 2 received BG alone and group 3 received no augmentation. Bone stability was assessed 1 and 2 years after non-union revision surgery through analysis of radiographs using the Lane Sandhu Score. Scores ≥ 3 were rated as stable Other influencing factors were collected from the electronic medical record.Results: In 224 non-unions, bone defects were filled with autologous bone and TCP (TCP+BG). In 137 non-unions, bone defects were filled with autologous bone (BG), and in 43 non-unions presenting non-relevant defects, neither autologous bone nor TCP were used (NBG). After 2 years, 72.7% of the TCP+BG patients, 90.1% of the BG patients and 84.4% of the NBG patients achieved a consolidation score ≥ 3. Advanced age, presence of comorbidities and longer treatment period had a significantly negative effect on consolidation 1 year after surgery. Longer treatment periods also showed a negative significant effect after 2 years. It is notable that larger defects, mainly treated with the combination of autologous bone and TCP, showed similar healing rates to that of smaller defects after 2 years.Conclusion: The combination of TCP and autologous bone-grafts shows good results in the reconstruction of complicated bone-defects, but patience is required since the healing period exceeds 1 year in most patients.Keywords: non-unions, bone substitute, Lane Sandhu Score, tricalcium phosphate